PERCEPTION OF NURSING MOTHER ABOUT THE BREAST MILK BANKIN MOTHER AND CHILD HOSPITAL IN BLANG PADANG,BANDA ACEH IN 2013 - Irmawati Irmawati; Marniati Marniati; Rahmayani Rahmayani (JOURNAL OF HEALTHCARE TECHNOLOGY AND MEDICINE, 2015)
The results obtained from interview to 10 nursing mothers. When being asked about their opinion of the Breast Milk Bank, 2 women answered that Breast Milk Bank is the place to storage breast milk, because they got information from the health officers and browsed in internet. While 8 other women did not know about the Breast Milk Bank. The research was conducted to know about nursing mother perception about the breast milk bank in mother and child hospital in  Blang Padang Banda Aceh in 2013. The research was conducted on August, 24th – 30th, 2013. This is a descriptive study by using cross-sectional approach to 69 respondents who breastfeed by distributing questionnaires. The results showed that from 69 respondents, 41 people (59.4%) have a positive perception and 28 people (40.6%) have negative perceptions. It is meant that the available of Breast Milk Bank in Mother and Child Hospital in Blang Padang is positive. This result is expected to become the input and information for nursing mothers about Breast Milk Bank.Keywords: Perception, nursing mothers, Breast Milk Bank